Synthesis and Antihistaminic Activity of Novel 2-Alkylamino and 2-Dialkylaminomethylthieno[2,3-d]pyrimidines - Shirole, N.L.; Talele, G.S.; Fursule, R.A.; Surana, S.J.; Jain, K.S. (Asian Journal of Chemistry, 2010)
Synthesis of a series of novel 2-piperazinyl and substituted piperazinylthieno[2,3- d]pyrimidines (Ia-j) for antihistaminic activity was undertaken through the reaction of piperazine and N-substituted piperazines with corresponding 2-methylthio and 2- chloromethylthieno[2,3-d]pyrimidin-4(3H)-ones. The compounds were evaluated for H1- receptor activity, in-vitro, through the inhibition of histamine induced goat trachea isotonic contraction method. The compounds Id, Ic and If, exhibited most significant activities amongst all the evaluated compounds and total six compounds were much superior to diphenhydramine (higher pA2 values).